Pascal Pyramids: a mathematical exploration using spreadsheets - John E Baker (Spreadsheets in Education, 2013)
The features of Pascal’s Triangle are generalised to 3-variable and 4-variable expressions resulting in the formation of pyramids of coefficients. The steps required to create the coefficients are also given.